2012
DOI: 10.1039/c1ra00525a
|View full text |Cite
|
Sign up to set email alerts
|

Pair distribution function analysis and Mössbauer study of defects in microwave-hydrothermal LiFePO4

Abstract: Olivine-type LiFePO 4 is nowadays one of the most important cathode materials of choice for highenergy lithium ion batteries. Its intrinsic defectivity, and chiefly the so-called lithium iron anti-site, is one of the most critical issues when envisaging electrochemical applications. This paper reports a combined diffractometric (Synchrotron Radiation XRD with Rietveld and PDF analyses) and spectroscopic (Mö ssbauer) approach able to give a thorough characterization of the material defectivity. Such analytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 47 publications
3
13
0
Order By: Relevance
“…also found the similar results about the antisite defects . The concentration and distribution of antisite defects observed by experimental procedures are in the range of 1–10 %, depending on different experimental conditions, such as the synthesis route, particle size, and temperature ,,…”
Section: Introductionsupporting
confidence: 66%
See 1 more Smart Citation
“…also found the similar results about the antisite defects . The concentration and distribution of antisite defects observed by experimental procedures are in the range of 1–10 %, depending on different experimental conditions, such as the synthesis route, particle size, and temperature ,,…”
Section: Introductionsupporting
confidence: 66%
“…Moreover, antisite defects are possible in the LiFePO 4 at higher temperature if sufficient calcination time and required inert gas atmosphere are not available during calcination. Though, exact reason of defects formation in LiFePO 4 is still not clear, but according to previous studies reported,,,, there are many factors viz. calcination time, temperature, synthesis process etc.…”
Section: Resultsmentioning
confidence: 98%
“…Microwave synthesis has emerged as an important technique for preparing materials, offering higher reaction rates, better selectivities and shorter reaction time compared to conventional thermal methods. [25][26][27][28][29] Though several kinds of nanoscale molybdates have been successfully synthesized using this technique, 30,31 the reported methods involve utilizing a solvent.…”
mentioning
confidence: 99%
“…Since the standard fitting procedure based on Lorentzian profiles and linear approximation generally leads to erroneous evaluation of weak and/or poorly resolved contributions4546, we chose to express the spectra line shape through the transmission integral function44 in order to take simultaneously all the broadening/distortion effects into account47.…”
Section: Methodsmentioning
confidence: 99%